(3QSGdI Hfi CHj MeGQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce SHMGfg hJYGdi Yf UaGJ Ndbg GdQO Ydi ef bGd Ef GdUhQI GdeSeGI HGdMGce EfJbdJ Edi GdUhQI GdeSeGI s
(3BNQgG (B:s
(3SHMGf ehdGfG YeG jXfhf hJfRg YeG jUa GdhGUahf hgh MSHi hfYe GdfUjQ GdeYjf , hHg ai LejY GdCehQ fSJYjf JeJ hGdMeO dehdGfG hMOg hGdTcQ dbGFe GdReGf YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B44s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds